Aplikasi Sistem Pakar untuk Diagnosa Penyakit Hipertiroid dengan Metode Inferensi Fuzzy Mamdani - Kamsyakawuni, Ahmad; Gernowo, Rachmad; Sarwoko, Eko Adi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
Medical  diagnosis  is  a  complex  issue  that  is  influenced  by  various  factors  and  settlement  involving  all  the  capabilities  of  experts, including expert intuition owned. Diagnosis of thyroid disease is difficult,  because the symptoms of thyroid disease can vary greatly, depending  on  the  ups  and  downs  of  thyroid  hormones.  This  study  applies  an  expert  system  for  diagnosis  of  hyperthyroidism  using Mamdani fuzzy inference methods. Expert system expertise needed to gain knowledge from the experts in resolving hyperthyroidism diagnosis  while  Mamdani  fuzzy  inference  is  used  for  the  processing  of  knowledge  in  order  to  obtain  the  consequence  or  conclusion which is the result of diagnosis. The process ofMamdani fuzzy inference in this study began with the formation of fuzzy set continued with the application process implications functions, then the composition rule and ending with defuzzyfication process. An expert system for the diagnosis of hyperthyroidism that has been applied with a symptom score of the input data, the results of the blood t ests TSHs level and FT4 levels, output data in the form of diagnosis, the diagnosis has been successfully  for tested the input data, with an accuracy of 95.45%.Keywords: Expert systems; Fuzzy inference Mamdani; Hyperthyroidism